Analisis Waktu Kegiatan Bongkar Muat Peti Kemas Terhadap Produktivitas BSH (Box Ship Hour) Untuk Mencapai Throughput Terminal Berlian Surabaya - Attijani, Irfan; Sutini, Sutini; Ihkamuddin, Zihni (Jurnal Global Ilmiah, 2025)
This study aims to analyze the effect of container loading and unloading time on Box Ship Hour (BSH) productivity at the Berlian Terminal in Surabaya and to identify the factors that influence it. The Berlian Terminal is the busiest domestic container terminal at the Port of Tanjung Perak in Surabaya, with a container flow of approximately 1 million TEUs per year. Primary data was obtained from PT Berlian Jasa Terminal Indonesia during 2024, with the MV. Oriental Diamond and MV. Oriental Galaxy as the sample vessels. The research method used a quantitative descriptive approach, including calculations of BSH and Box Crane Hour (BCH) productivity, as well as the identification of Idle Time and Not Operating Time. The results of the study show that the MV. Oriental Diamond had a total Idle Time of 97.22 hours, while MV. Oriental Galaxy had 73.68 hours. The average BSH Gross of both vessels did not meet the terminal's target of 22 boxes per hour, with MV. Oriental Diamond at 19.14 boxes per hour and MV. Oriental Galaxy (19.8 boxes/hour). As a result, PT BJTI experienced a productivity loss of 2,141 boxes/2,569 TEUs (MV. Oriental Diamond) and 1,621 boxes/1,945 TEUs (MV. Oriental Galaxy). The research conclusion indicates that idle time and operational constraints significantly impact loading and unloading productivity. The recommendations proposed include improving the efficiency of loading and unloading equipment, optimizing scheduling, and improving time management to achieve terminal throughput targets.